Numerical analysis of seismically induced liquefaction in earth embankment foundations. Part I. Benchmark model - Aydingun, O; Adalier, K (Canadian Science Publishing, 2003)
A numerical analysis has been performed for a clayey embankment founded on a liquefiable foundation soil using an effective stress based, fully coupled, finite element code called DIANA-SWANDYNE II. The results were compared with data obtained from centrifuge experiments. In Part I, the numerical method and the analysis procedure are explained. The results obtained for a series of three consecutive, increasing amplitude shaking events are presented. An attempt has been made to calibrate a benchmark model to be used in the application of different remedial measures which are discussed in Part II. The numerical predictions compared well with the experimental data and provided further insights into the dynamic behavior of embankment-foundation systems.
Keywords: liquefaction; numerical modeling; coupled formulation; centrifuge; embankment; earthquakes